2009
DOI: 10.1007/s11255-009-9545-x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of the tyrosine kinase inhibitor in a peritoneal dialysis patient with metastatic renal cell carcinoma: possible beneficial effects on peritoneal membrane and peritonitis rates

Abstract: Increased submesothelial collagen deposition, loss of mesothelial cells and increased peritoneal vascularization of peritoneal membrane with vasculopathy leads to peritoneal fibrosis in a patient on long-term peritoneal dialysis (PD). This vascular proliferation within the peritoneum is associated with an increased expression of vascular endothelial growth factor (VEGF), which in turn leads to functional loss or deterioration of the peritoneal membrane over time. Vascular endothelial growth factor inhibitors m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…However, sunitinib treatment further increased the PD-induced VEGF levels. This has also been published by others and could be explained by a lack of degradation due to blocking of the VEGF receptor signalling [55,56] . Interestingly, a loss of mast cells in the mesentery was observed in the sunitinib-treated animals.…”
Section: Prevention Of Pd-induced Angiogenesissupporting
confidence: 69%
See 1 more Smart Citation
“…However, sunitinib treatment further increased the PD-induced VEGF levels. This has also been published by others and could be explained by a lack of degradation due to blocking of the VEGF receptor signalling [55,56] . Interestingly, a loss of mast cells in the mesentery was observed in the sunitinib-treated animals.…”
Section: Prevention Of Pd-induced Angiogenesissupporting
confidence: 69%
“…Sunitinib is a tyrosine kinase inhibitor and involved in the inhibition of VEGF and platelet-derived growth factor receptor signalling. A case study performed by Tapiawala et al [55] showed a positive effect of a PD patient treated with sunitinib against metastatic renal cell carcinoma. The patient's peritoneal permeability remained stable even over 10 years.…”
Section: Prevention Of Pd-induced Angiogenesismentioning
confidence: 99%
“…Agents such as pirfenidone (inhibits the expression of TGF-beta 1 and TNF-alpha and scavenges reactive oxygen species) [42], antiangiogenic strategies with anti-VEGF neutralizing antibodies [43], TPN-470 [44] and endostatin peptide [45] as well as oligonucleotides against the collagen accumulating heat shock protein 47 (HSP-47) [46], ONO 487 (reduces the expression of MMP-2, TGF-beta and VEGF and subsequent accumulation of type I collagen) [47], chimeric DNA–RNA hammerhead ribozyme targeting TGF-beta mRNA [48] and hepatocyte growth factor [49] are discussed. Stabilization of D/P creatinine over time on PD has also been reported in a PD patient with metastatic renal cell carcinoma treated with the tyrosine kinase inhibitor sunitinib that also has anti-VEGF effects [50]. …”
Section: Experimental Data On Medical Treatment For Epsmentioning
confidence: 96%
“…Another kind of VEGF inhibitors are the tyrosine kinase inhibitors, such as Sunitinib, which is able to block the VEGF signaling. Indeed, it has been observed that its administration to a female PD patient with end stage renal disease and metastasic renal cell carcinoma helps to stabilize the abdominal metastasis as well as the thickness of the PM, and the D/P creatinine ratio remains stable [100].…”
Section: Vegfmentioning
confidence: 99%